Between Vanity and Sensitiveness: Indo–British Relations During Vijayalakshmi Pandit's High-Commissionership (1954–61). Issue 1 (2nd January 2016) - Ankit, Rakesh
Abstract : Studies of Indo–British relations in the 1950s have been usually dominated by the personalities of Jawaharlal Nehru and, after him, VK Krishna Menon. This article instead focuses on Vijayalakshmi Pandit and her tenure as India's High-Commissioner in London. Pandit came to London having served as Nehru's envoy to the Soviet Union, the USA and the United Nations. Based on government records and private papers in India, Britain and America, this article shows that her time in London offers insights into the wider context of changes in Indo–British relations and presents her High-Commissionership as a microcosm of the inter-governmental relations.